Cosmos: a system of thought - Mouzouropoulos, Theseas (My University, 2021)
We–think is much more important than i–think Our species’ extraordinary evolutionary success is largely driven by our ability to think socially, to learn socially and to embed that thinking and learning in culture so that others we have never met can also take advantage of it: “WE-think is much more important than I-think” Mark Earls, Protein Journal, April 2010
Keywords: Graphic Design; poster design